Activation of protein kinases and inhibition of protein phosphatases play a central role in the regulation of exocytosis in mouse pancreatic beta cells. - Ammälä, C; Eliasson, L; Bokvist, K; Berggren, P; Honkanen, R; Sjöholm, A; Rorsman, P (1994)
The mechanisms that regulate insulin secretion were investigated using capacitance measurements of exocytosis in single beta cells maintained in tissue culture. Exocytosis was stimulated by voltage-clamp depolarizations to activate the voltage-dependent Ca2+ channels that mediate Ca2+ influx into the beta cell. Under basal conditions, the exocytotic responses were small despite large Ca2+ currents. The exocytotic responses were dramatically increased (10- to 20-fold) by conditions that promote protein phosphorylation, such as activation of protein kinases A and C or inhibition of protein phosphatases. The stimulation of secretion was not due to an enhancement of Ca2+ influx and both peak and integrated Ca2+ currents were largely unaffected. Our data indicate that exocytosis in the insulin-secreting pancreatic beta cell is determined by a balance between protein phosphorylation and dephosphorylation. They further suggest that although Ca2+ is required for the initiation of exocytosis, modulation of exocytosis by protein kinases and phosphatases, at a step distal to the elevation of Ca2+, is of much greater quantitative importance. Thus an elevation of Ca2+ may represent a permissive rather than a decisive factor in the regulation of the insulin secretory process.